Providing Privacy in Geosocial Networks - N., Priyanka (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2015)
Social Network providers concentrate more on profit. Users reveal their personal information and make themselves into trouble. So a framework is proposed to face the conflict between the privacy and profit. The framework that consists of Location Profiles and a venue centric profiles and decentralized approach is provided for strong privacy and also implemented in android.